Implementation of Project-Based Model in Collaborative Distance Learning System for Second Grade Elementary School - Elis Listiani; Achmad Supriyanto; Muhammad Hanif (EduBasic Journal: Jurnal Pendidikan Dasar, 2021)
The COVID-19 pandemic has had a major impact on the education sector, especially for schools, in the form of a change in the learning process, which currently must be done in a different space and distance. In areas with a harmless zone and inadequate for online learning, the schools have practiced two ways of learning: face-to-face and non-face-to-face. The scientific model should still be implemented eventhough in distance learning situation. This study aimed to examine the use of a project-based learning model for elementary school students to develop a collaborative distance learning system during the COVID-19 pandemic. The research method employed classroom action research from the John Elliot model. The first cycle of learning was carried out online, and the second cycle of learning was conducted face-to-face at school. The research was done in two cycles because students had limited facilities to support online learning. The data collection technique was through observation. The research subjects involved were second-grade elementary school students of SD Negeri 2 Kurung Kambing in Pandeglang Regency. This study’s results proved that the project-based model influenced increasing psychomotoric competency achievement in the SBdP (Cultural Arts and Crafts) subject with teaching materials mimicking daily and natural movements in the "Planting Corn" dance. This learning also involved students more actively and trained them to think critically and behave creatively.